Size Aftereffects Are Eliminated When Adaptor Stimuli Are Prevented from Reaching Awareness by Continuous Flash Suppression - Laycock, Robin; Sherman, Joshua A.; Sperandio, Irene; Chouinard, Philippe A. (Frontiers in Human Neuroscience, 2017)
Size aftereffects are a compelling perceptual phenomenon in which we perceive the size of a stimulus as being different than it actually is following a period of visual stimulation of an adapter stimulus with a different size. Here, we used continuous flash suppression (CFS) to determine if size aftereffects require a high-level appraisal of the adapter stimulus. The strength of size aftereffects was quantified following a three-second exposure to perceptually visible and invisible adapters. Participants judged the size of a target that followed the adapter in comparison to a subsequent reference. Our experiments demonstrate that the adapter no longer influenced the perceived size of the subsequent target stimulus under CFS. We conclude that the perception of size aftereffects is prevented when CFS is used to suppress the conscious awarness of the adapting stimulus.